Leadership, proactive behavior and innovative work behaviors of teachers in Barkin-Ladi - Dung, Kim Dawang (Annals of Management and Organization Research, 2024)
Purpose: This study examines the effects of leadership styles and proactive behavior on the innovative work behaviors of private school teachers in Barkin, Ladi, and Plateau states. Research Methodology: The study drew a sample of private schoolteachers in Barkin-ladi using a quota sampling technique. The sample numbered 201, being male (82) and female (119), between the ages of 15 and 64 years, with different levels of educational qualification. The scales deployed in measuring innovative work behaviour, proactive behavior, and leadership styles were already standardized scales that were designed to measure the constructs in school settings. Results: The study found that the sampled teachers exhibited all leadership styles: transformational, transactional, and laissez. Leadership styles and proactive work behavior had a significant effect on teachers’ innovative work behaviors. There was no significant interaction effect between leadership style and proactive work behavior on innovative work behavior. Limitations: The sample size of this study was limited because the actual population was uncertain. Contribution: This study shows that transformational and transactional leadership styles, as well as proactive work behaviors, are important to provoke teachers’ innovative work behaviors in private schools in Barkin-ladi. Novelty: The study has been able to show the teacher plays the role of the leader in the class and his innovative teaching behaviour is provoked by proactive behaviours and transformational/transactional leadership styles.